PELAYANAN KESEHATAN DI PUSKESMAS GOlAGO KUSUMA KECAMATAN SAHU TIMUR KABUPATEN HALMAHERAT BARAT - TOODY, JESISKA; RURU, JOORIE; PALAR, NOVIE (Sam Ratulangi University, 2022)
This study was conducted to determine whether the health care facilities at the Golago Kusuma HealthCenter have provided services that are in accordance with the expectations of patients or the community.The research method used is a qualitative method with interview data collection techniques. The theoryused in health services consists of input, process, output, impact and feedback, all of which areinterconnected and influence each other. Data collection techniques used in this study are: Interview,Observation, and Documentation of data obtained from various sources and then analyzed which becomesa conclusion from the research process. The results obtained from this study indicate that health servicesat the Puskesmas are still many obstacles encountered in terms of inadequate facilities and infrastructure,incomplete medicines produce an ineffective impact because of the many obstacles that occur in service tothe community public.Keywords: Health Services Puskesmas.